Simulation Technique of Steady-State Network based on AODV Routing Protocol - Ayanwuyi, Kolade T.; Zuhairi, Megat F.; Zheng, C. L.; Alias, Irma S.C (International Journal of Engineering and Technology, 2018)
Wireless network refers to any characteristic of a computer network that does not depend on line connectors or physical connections. One of the outstanding characteristic of wireless Mobile Ad hoc Network (MANET) that is significantly different compared to the traditional wired networks is mobility. A user i.e. typically represented by a mobile station or nodes can freely move, whilst being connected to the network. Generally, MANET is a collection of wireless mobile nodes that possess the ability to intercommunicate with one another without any predefined infrastructure or centralized administration support [1]. They are self-organized, autonomous and decentralized multi-hop wireless system of mobile nodes [2]. As such, a reliable MANET routing protocol is needed to enable data to be propagated multi-hops. An example of such routing protocol is Ad hoc On Demand Distance Vector (AODV). Using AODV as the basis of this work, this research paper discusses the best approach to conduct simulation experiment particularly for discrete-event based simulator such as Network Simulator. The underlying principle in MANET simulation is to ensure results are as credible to the empirical experiment. Therefore, iteration of experiment is essential to determine the final result. Much research work also fails to identify the existence of transient phase in simulation work. Failure to address the issue may cause inconsistent result. In addition, a validation methodology based on comparison method is also presented. Although such technique is fairly common, it is one of the most effective method to assess the reliability of the simulation tool.